Comparison of thulium laser en bloc resection of bladder tumor and transurethral resection of bladder tumor on catheter-related bladder discomfort- a single center experience - Gao, Wenbo; Ye, Haihon; Huang, Jiawen; Chen, Telei (Oncology Reviews, 2025)
ObjectiveTo Compare the effects between thulium laser en bloc resection of bladder tumor (ERBT) and conventional transurethral resection of bladder tumor (TURBT) on catheter-related bladder discomfort (CRBD) in patients with bladder cancer.MethodsBetween January 2022 and December 2024, we retrospectively collected the demographic and clinical data for patients with bladder cancer. A total of 79 patients in the conventional TURBT group and 58 patients in the thulium laser ERBT group completed the study. Both demographic and outcome variables were recorded; and we compared the incidence and severity of CRBD at 1, 6 and 24 h postoperatively, score of postoperative pain at 1, 6 and 24 h and patient satisfaction at 24 h following the surgery.ResultsThere were no significant differences in age, gender proportion, tumor multiplicity, tumor size and location, and duration of surgery between the two groups (P > 0.05). Pathological examination revealed that the ERBT had a higher rate of detrusor presence than TURBT (P = 0.04). The incidence and severity of postoperative CRBD were lower in ERBT group than TURBT group at 1 and 6h (P < 0.001), while there were no statistically significant difference between the two groups (P = 0.17) at 24 h. The VAS scores of postoperative pain were significantly lower in ERBT group than in TURBT group at 1 and 6 h postoperatively (P = 0.001 and P = 0.02, respectively). But at 24 h, there was no statistically significant difference (P = 0.08). As to postoperative patient satisfaction at 24 h, the result of ERBT group was significantly lower than TURBT group (P = 0.02). Additionally, the ERBT group had significantly less intraoperative blood loss and shorter postoperative irrigation duration (P = 0.001). No significant difference was found in the duration of indwelling catheter between the two groups (P = 0.07).ConclusionThe results suggest that compared to conventional TURBT, thulium laser ERBT significantly reduce CRBD incidence and severity, lower postoperative pain, and improve postoperative patient satisfaction. However, as a single-center retrospective study, these findings require further validation by large-scale, prospective, multicenter trials.